A Continuous Trust-Region-Type Method for Solving Nonlinear Semidefinite Complementarity Problem - Ying Ji; Tienan Wang; Yijun Li (Abstract and Applied Analysis)
We propose a new method to solve nonlinear semidefinite complementarity problem by combining a continuous method and a trust-region-type method. At every iteration, we need to calculate a second-order cone subproblem. We show the well-definedness of the method. The global convergent result is established.